SABCS 2017: lifestyle factors, hormone receptor-positive advanced disease, liquid biopsies, and prognosis - Rinnerthaler, Gabriel (Memo, 2018)
This article reviews the clinically most relevant presentations at the San Antonio Breast Cancer Symposium (SABCS) 2017 on the topics lifestyle factors, hormone receptor-positive advanced disease, liquid biopsies, and prognosis. In a retrospective analysis of the Women’s Health Initiative Observational Study, a reduction in the body mass index (BMI) of at least 5% within 3 years significantly reduced the risk of breast cancer compared to women with a stable weight (HR 0.77; 95% CI 0.78–0.98). In the MONALEESA-7 trial investigating ribociclib or placebo in combination with endocrine therapy as first-line treatment in pre- and perimenopausal women with hormone receptor-positive, human epidermal growth factor 2 (HER2)-negative metastatic breast cancer, a significantly longer progression-free survival was shown for patients treated with ribociclib compared to the placebo group (23.8 vs. 13.0 months; HR 0.55; 95% CI 0.43–0.72; P < 0.001). In a pooled toxicity and efficacy analysis of elderly women treated with a cyclin-dependent kinase 4/6 (CDK4/6) inhibitor in combination with an aromatase inhibitor in first-line, toxicities of higher grade were more common in elderly compared to younger patients, despite comparable efficacy. And the Clinical Treatment Score post-5 years (CTS5), accurately estimated the risk of late recurrence after 5 years of adjuvant endocrine treatment using routinely available clinical parameters.